Anticandidal Activity of Lactoferrin, Apolactoferrin, and Oligosaccharides on Mueller-Hinton and Sabouraud Dextrose Agar against Fluconazole Resistant-Candida Albicans - Maureen Miracle Stella; Sem Samuel Surja; Zita Arieselia (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: The demand for novel, useful, potential, and safe antifungal drugs and rapid fungal susceptibility test methods due to antifungal resistance and high prevalence of Candida albicans infection are continuing. Therefore, this study aimed to assess and compare the antifungal activity of lactoferrin, apolactoferrin, and oligosaccharides isolated from human, bovine, goat, and formula milk against C. albicans on Mueller-Hinton agar supplemented with 2% glucose and 5 µg/mL methylene blue and sabouraud dextrose agar.Methods: Lactoferrin, apolactoferrin, and oligosaccharides were extracted from human, bovine, goat, and formula milk. Lactoferrin was identified using the Bradford test and Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis. Oligosaccharides were identified using Thin-Layer Chromatography. The antifungal activity of lactoferrin, apolactoferrin, and oligosaccharides against fluconazole-resistant Candida albicans ATCC 10231 was determined and compared using the disk diffusion method on Mueller-Hinton agar and sabouraud dextrose agar. The inhibition zone formed around the disk was observed after 24 hours of incubation.Results: Lactoferrin showed an inhibition zone on sabouraud dextrose agar against C. albicans, but not on Mueller-Hinton agar. Meanwhile, apolactoferrin and oligosaccharides showed no antifungal activity on both agar media.Conclusions: Different agar media in the diffusion disk test can give different results even though using the same test method and substance. These results could shed light and become the useful references on why some potential antifungals could yield a different results in in-vitro studies, in-vivo studies, or clinical trials.